High-intensity interval training (HIIT) effectively enhances heart function via miR-195 dependent cardiomyopathy reduction in high-fat high-fructose diet-induced diabetic rats. (26th May 2020) - Khakdan, Soheyla; Delfan, Maryam; Heydarpour Meymeh, Maryam; Kazerouni, Faranak; Ghaedi, Hamid; Shanaki, Mehrnoosh; Kalaki-Jouybari, Fatemeh; Gorgani-Firuzjaee, Sattar; Rahimipour, Ali
Abstract: Aims: Regarding the fact that up-regulation of miR-195 in diabetic hearts has a potential role in diabetic cardiomyopathy, the present study investigated whether continuous endurance training (CET) and high-intensity interval training (HIIT) reduces miR-195 expression and which exercise is effective in this regard. Methods: Diabetes was induced by high-fat high-fructose diet (HFHFD). Then, the rats were sub-divided into three categories; sedentary (HFHFD + SED), continuous endurance training (HFHFD + CET), and high-intensity interval training group (HFHFD + HIIT). After eight weeks of running, expression of miR-195 and myocardial function were evaluated. Results: HIIT effectively decreases the expression of miR-195 and increases the expression of Sirt1 and BCL-2 in diabetic rats compared with CET. Our results showed that HIIT compared with CET increases left ventricular ejection fraction (LVEF%) and fractional shortening (FS%). Conclusions: Our results indicated that exercise, especially HIIT is an appropriate strategy for reducing miR-195 and improving myocardial function in diabetic rats compared with CET.